Effect of adolescent pregnancy on maternal and foetal health - Lewis, Preeti F.; Nakhare, Vedangee R.; Bavdekar, Nitin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Adolescence is a time when structural, functional, and psychosocial developments occur. Pregnancy during teenage can adversely affect the health of both the mother and the foetus as the adolescent female concerned is yet to attain her full growth potential. Adolescent pregnancy is a global phenomenon with serious health, social and economic consequences. Methods: It was a single centric, prospective, observational study. 211 Patients who attended the inpatient or outpatient department of obstetrics and gynaecology in an urban tertiary care hospital and followed up till outcome. Results: As per the study conducted, almost 83% of teenage mothers conceive by 19 years of age. Owing to the increasing awareness regarding maternal and foetal wellbeing, majority of the teenage mothers were booked. Teenage mothers and their babies are prone to intrapartum and postpartum complications as well as stillbirths. The most common comorbidity associated in teenage mothers was pregnancy induced hypertension (PIH) spectrum disorders followed by anaemia. The rate of neonatal intensive care unit (NICU) admission for babies of teenage mothers was 10%. Conclusions: Adolescent mothers and their babies are at a risk of complications than other mothers in the twenties. The need of the hour are comprehensive measures and convergence among various departments to address all the needs of adolescents. Robust measures and policies to end teenage marriages and consequent pregnancies are exactly what the developing nations need at present.